Rhizosphere ecology of lumichrome and riboflavin, two bacterial signal molecules eliciting developmental changes in plants - Dakora, Felix D.; Matiru, Viviene; Kanu, Alfred S. (Frontiers in Plant Science, 2015)
Lumichrome and riboflavin are novel molecules from rhizobial exudates that stimulate plant growth. Reported studies have revealed major developmental changes elicited by lumichrome at very low nanomolar concentrations (5 nM) in plants, which include early initiation of trifoliate leaves, expansion of unifoliate and trifoliate leaves, increased stem elongation and leaf area, and consequently greater biomass accumulation in monocots and dicots. But higher lumichrome concentration (50 nM) depressed root development and reduced growth of unifoliate and second trifoliate leaves. While the mechanisms remain unknown, it is possible that lumichrome released by rhizobia induced the biosynthesis of classical phytohormones that caused the observed developmental changes in plants. We also showed in earlier studies that applying either 10 nM lumichrome, 10 nM ABA, or 10 ml of infective rhizobial cells (0.2 OD600) to roots of monocots and dicots for 44 h produced identical effects, which included decreased stomatal conductance and leaf transpiration in Bambara groundnut, soybean, and maize, increased stomatal conductance and transpiration in cowpea and lupin, and elevated root respiration in maize (19% by rhizobia and 20% by lumichrome). Greater extracellular exudation of lumichrome, riboflavin and indole acetic acid by N2-fixing rhizobia over non-fixing bacteria is perceived to be an indication of their role as symbiotic signals. This is evidenced by the increased concentration of lumichrome and riboflavin in the xylem sap of cowpea and soybean plants inoculated with infective rhizobia. In fact, greater xylem concentration of lumichrome in soybean and its correspondingly increased accumulation in leaves was found to result in dramatic developmental changes than in cowpea. Furthermore, lumichrome and riboflavin secreted by soil rhizobia are also known to function as (i) ecological cues for sensing environmental stress, (ii) growth factors for microbes, plants, and humans, (iii) signals for stomatal functioning in land plants, and (iv) protectants/elicitors of plant defense. The fact that exogenous application of ABA to plant roots caused the same effect as lumichrome on leaf stomatal functioning suggests molecular cross-talk in plant response to environmental stimuli.